A Cu 0 -CuFe x O y Iron-copper bimetallic composite and preparation method and application thereof
By preparing Cu0-CuFexOy iron-copper bimetallic composite, the problems of oxide film blocking, Fe ion spillover and insufficient catalytic capacity of existing iron-based materials when activating persulfate are solved, and the effect of efficiently removing OTC in water is achieved.
Patent Information
- Application Number
- CN202411694005.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
When the existing iron-based materials activate persulfates to remove antibiotic pollutants, there are problems such as surface oxide film blocking electron mass transfer and Fe ion spillover resulting in poor stability and insufficient catalytic capacity.
Cu0-CuFexOy iron-copper bimetallic composite was prepared, and Cu0-CuFexOy material with a Fe:Cu molar ratio of 2:1 was pre-prepared, pH value was adjusted, carbon nanotubes and KBH4 were added, sol reaction and high temperature treatment were carried out to obtain Cu0-CuFexOy material with a wide pH range and high catalytic activity.
It realizes the efficient activation of Cu0-CuFexOy material to remove OTC, with a large surface area and stability, has a wide pH range, and has a fast electron mass transfer efficiency, which is suitable for efficient removal of antibiotic pollutants in water bodies.
Smart Images

Figure CN119186565B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of composite materials, and in particular to a Cu 0 -CuFe x O y Iron-copper bimetallic composite and preparation method and application thereof. Background Art
[0002] Oxytetracycline (OTC) is a typical tetracycline antibiotic. It is widely used in life because of its broad-spectrum and low price. However, traditional sewage treatment methods cannot completely degrade and remove it. There is often a certain amount of residue in the effluent of treatment facilities, resulting in frequent detection of OTC in surface water and even drinking water. At the same time, the large-scale use of OTC has also brought many social and environmental problems, such as damaging the ecological environment, leading to the emergence of drug-resistant bacteria, causing abnormal liver and kidney function in humans, and affecting the human immune system.
[0003] Since OTC has polar groups such as hydroxyl groups, it is easy to aggregate in water bodies. For the removal of OTC in water bodies, the current treatment methods can be roughly divided into physical methods, chemical methods, biological methods and other methods. Permonosulfate (PMS) advanced oxidation technology (AOPs) has received widespread attention. Iron-based materials are often used to activate persulfate to remove antibiotic pollutants (such as oxytetracycline, OTC, etc.) in wastewater because of their wide sources, low prices, and high catalytic ability. However, iron-based materials such as Fe 0 There are three main problems in the process of persulfate activation: (1) Fe 0 The surface of the material is prone to form an oxide film that blocks electron transfer, making the pH range of the material narrow; (2) The large amount of Fe ions overflowing during the reaction makes the stability of the iron-based material relatively poor; (3) Fe 2+ / Fe 3+ The valence state cycling ability is poor and its catalytic ability needs to be further improved. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a Cu 0 -CuFe x O y Iron-copper bimetallic composite and preparation method and application thereof.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A Cu 0 -CuFe x O yThe preparation method of the iron-copper bimetallic composite comprises the following steps:
[0007] S1. Prepare a mixed solution of Fe(NO3)3 and Cu(CH3COO)2 with a molar ratio of Fe:Cu of 2:1 in advance, and adjust the pH value of the solution to 9;
[0008] S2, according to the amount of the mixed solution in S1, add carbon nanotubes in an amount of 2.5-5g / L, stir evenly, then add KBH4 in an amount of 2.5-5g / L, and stir evenly, wherein the KBH4 is prepared into a solution and added dropwise;
[0009] S3, after the KBH4 solution was added, the reaction was continued at 90°C with stirring for 4 h to obtain Cu 0 -CuFe x O y Sol;
[0010] S4, the obtained Cu 0 -CuFe x O y The sol was subjected to high temperature treatment, calcined at 400-600°C, and kept at this temperature for 180 min to obtain Cu 0 -CuFe x O y Material.
[0011] Specifically, in S1, ammonia water is used to adjust the pH.
[0012] In S3, the reaction temperature was maintained at 90° C. by water bath heating and mechanical stirring for 4 h.
[0013] The initial temperature rise rate in S4 is 10°C / min.
[0014] A second aspect of the present invention provides a Cu 0 -CuFe x O y The iron-copper bimetallic composite is prepared by the above preparation method, and the prepared composite is filled with nitrogen for protection.
[0015] A third aspect of the present invention provides a Cu 0 -CuFe x O y The application of iron-copper bimetallic complex in persulfate advanced oxidation technology has a pH range of 3-11.
[0016] Cu 0 -CuFe x O y The / PMS system mainly relies on the synergistic effect of the two metals and a small amount of overflowed metal ions to catalyze PMS to produce active species: O2 •- 、SO4•- and OH•and 1 O2, where 1 O2 plays a major role, and the main reaction equation is as follows:
[0017]
[0018] The Cu provided by the present invention 0 -CuFe x O y The main component of the iron-copper bimetallic composite is CuFe2O4, which also contains some copper compounds and iron oxides. The unique spinel structure of CuFe2O4 reduces the amount of Fe ion overflow, thereby improving the stability of the material; 0 Cu produced by corrosion + Can promote Fe 2+ / Fe 3+ The cycle of Cu 0 -CuFe x O y The iron-copper bimetallic complex has a large surface area, which allows the material to provide more active sites during catalysis.
[0019] The beneficial effects of the present invention are:
[0020] The present invention prepares Cu based on traditional iron-based materials. 0 -CuFe x O y The iron-copper bimetallic complex has the characteristics of simple preparation process, wide pH application range, fast electron mass transfer efficiency, good stability, strong activation ability, etc., which provides an effective way to efficiently activate PMS to remove OTC. Iron, copper, and carbon materials (carbon nanotubes) are used as raw materials. Iron has magnetic properties and is easy to separate and recycle. The raw materials are widely available and inexpensive. The sol-gel combustion technology is easy to operate, and the preparation method is simple to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Cu prepared in Example 1-5 0 -CuFe x O y The degradation effect of iron-copper bimetallic complex on OTC;
[0022] Figure 2 The degradation effect diagram of OTC by the materials prepared in the examples and comparative examples;
[0023] Figure 3 XRD patterns of the iron-copper bimetallic composites prepared by adding different reagents;
[0024] Figure 4 Cu0 -CuFe x O y XPS pattern of iron-copper bimetallic complex;
[0025] Figure 5 Cu 0 -CuFe x O y EDS Mapping of Fe element in iron-copper bimetallic complex;
[0026] Figure 6 Cu 0 -CuFe x O y EDS Mapping of Cu element in Fe-Cu bimetallic composite;
[0027] Figure 7 Cu 0 -CuFe x O y EDS Mapping of O element in Fe-Cu bimetallic complex;
[0028] Figure 8 Cu 0 -CuFe x O y EDS Mapping of C element of iron-copper bimetallic complex;
[0029] Fig. 9 This is the SEM surface morphology of the material obtained in Comparative Example 3;
[0030] Fig.10 This is the SEM surface morphology of the material obtained in Example 2;
[0031] Fig.11 Cu 0 -CuFe x O y Nitrogen isothermal desorption curve of iron-copper bimetallic composite;
[0032] Fig.12 Cu 0 -CuFe x O y The corresponding pore size distribution curve of the iron-copper bimetallic composite;
[0033] Fig.13 The electrochemical impedance analysis diagram of the materials prepared in the embodiment and the comparative example;
[0034] Fig.14 The effect of different initial pH on the degradation of OTC;
[0035] Fig.15 Cu0 -CuFe x O y Figure 2. Stability test results of iron-copper bimetallic composite. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] Weigh Fe(NO3)3 and Cu(CH3COO)2 to prepare a mixture of 1L with a molar ratio of Fe:Cu of 2:1. Use ammonia water to adjust the pH value of the solution to 9, then add 2.5gKBH4 to the mixture and continue stirring. After the KBH4 solution is added, keep it in a 90℃ water bath and stir it mechanically for 4h to obtain Cu 0 -CuFe x O y Sol. Cu 0 -CuFe x O y The sol was placed in a muffle furnace for high temperature treatment (heating rate 10 °C / min, holding time 180 min, calcination temperature 400 °C) to obtain Cu 0 -CuFe x O y The iron-copper bimetallic composite is filled with nitrogen for protection and is ready for use.
[0039] Example 2
[0040] Weigh Fe(NO3)3 and Cu(CH3COO)2 to prepare a 1L mixed solution with a molar ratio of Fe:Cu of 2:1. Use ammonia water to adjust the pH value of the solution to 9. Add 2.5g of carbon nanotube (CNT) material and stir for 3min to fully mix the metal ions and carbon nanotubes in the mixed solution. Then, drop 2.5g of KBH4 into the mixed solution and continue stirring. After the KBH4 solution is added, keep it in a 90℃ water bath and stir it mechanically for 4h to obtain Cu 0 -CuFe x O y Sol. Cu 0 -CuFe x O y The sol was placed in a muffle furnace for high temperature treatment (heating rate 10 °C / min, holding time 180 min, calcination temperature 400 °C) to obtain Cu 0-CuFe x O y The iron-copper bimetallic composite is filled with nitrogen for protection and is ready for use.
[0041] Example 3
[0042] Weigh Fe(NO3)3 and Cu(CH3COO)2 to prepare a 1L mixed solution with a molar ratio of Fe:Cu of 2:1. Use ammonia water to adjust the pH value of the solution to 9. Add 2.5g of carbon nanotube (CNT) material and stir for 3min to fully mix the metal ions and carbon nanotubes in the mixed solution. Then, drop 2.5g of KBH4 into the mixed solution and continue stirring. After the KBH4 solution is added, keep it in a 90℃ water bath and stir it mechanically for 4h to obtain Cu 0 -CuFe x O y Sol. Cu 0 -CuFe x O y The sol was placed in a muffle furnace for high temperature treatment (heating rate 10 °C / min, holding time 180 min, calcination temperature 600 °C) to obtain Cu 0 -CuFe x O y The iron-copper bimetallic composite is filled with nitrogen for protection and is ready for use.
[0043] Example 4
[0044] Weigh Fe(NO3)3 and Cu(CH3COO)2 to prepare a 1L mixed solution with a molar ratio of Fe:Cu of 2:1. Use ammonia water to adjust the pH value of the solution to 9. Add 2.5g of carbon nanotube (CNT) material and stir for 3min to fully mix the metal ions and carbon nanotubes in the mixed solution. Then, drop 5g of KBH4 into the mixed solution and continue stirring. After the KBH4 solution is added, keep it in a 90℃ water bath and stir it mechanically for 4h to obtain Cu 0 -CuFe x O y Sol. Cu 0 -CuFe x O y The sol was placed in a muffle furnace for high temperature treatment (heating rate 10 °C / min, holding time 180 min, calcination temperature 400 °C) to obtain Cu 0 -CuFe x O y The iron-copper bimetallic composite is filled with nitrogen for protection and is ready for use.
[0045] Example 5
[0046] Weigh Fe(NO3)3 and Cu(CH3COO)2 to prepare a mixture of 1L with a molar ratio of Fe:Cu of 2:1. Use ammonia water to adjust the pH value of the solution to 9. Add 5g of carbon nanotube (CNT) material and stir for 3min to fully mix the metal ions and carbon nanotubes in the mixture. Then, drop 2.5g of KBH4 into the mixture and continue stirring. After the KBH4 solution is added, keep it in a 90℃ water bath and stir it mechanically for 4h to obtain Cu 0 -CuFe x O y Sol. Cu 0 -CuFe x O y The sol was placed in a muffle furnace for high temperature treatment (heating rate 10 °C / min, holding time 180 min, calcination temperature 400 °C) to obtain Cu 0 -CuFe x O y The iron-copper bimetallic composite is filled with nitrogen for protection and is ready for use.
[0047] Comparative Example 1
[0048] Different from Example 2, when preparing the mixed solution, only cupric acetate is added without adding ferric nitrate, and the other preparation steps are the same as Example 2, to obtain Sample 1.
[0049] Comparative Example 2
[0050] Different from Example 2, when preparing the mixed solution, only ferric nitrate is added without adding copper acetate, and the other preparation steps are the same as Example 2 to obtain Sample 2.
[0051] Comparative Example 3
[0052] Different from Example 2, no carbon nanotubes and potassium borohydride were added during the preparation process, and Sample 3 was prepared.
[0053] test:
[0054] Take five groups of 200mL OTC reaction solution (initial OTC concentration is 20mg·L -1 ) were placed in a low-temperature thermostatic bath or a constant temperature water bath, the reaction temperature was controlled at 25°C, and the initial pH value of the reaction solution was adjusted to 3 using NaOH solution and dilute H2SO4 solution. 0 -CuFe x O y The iron-copper bimetallic complex was reacted with 25 mg / L and 0.1 mmol / LPMS, and the time was set. 3 mL of the sample was taken at the set time interval, quickly mixed with the reaction terminator (sodium thiosulfate), and the degradation effect of the sample on OTC was compared and analyzed by high performance liquid chromatography. The degradation results are shown in Figure 1 After 45 minutes, the degradation rate can reach more than 90%.
[0055] Take five groups of 200mL OTC reaction solution (initial OTC concentration is 20mg·L -1 ) were placed in a low-temperature thermostatic bath or a thermostatic water bath, the reaction temperature was controlled at 25°C, and the initial pH value of the reaction solution was adjusted to 3 using NaOH solution and dilute H2SO4 solution. 0 -CuFe x O y The iron-copper bimetallic composite and the samples prepared in comparative examples 1-3 were reacted at 25 mg / L with 0.1 mmol / L PMS, and the time was set. The control group was only added with PMS. 3 mL of the sample was taken at the set time interval, quickly mixed with the reaction terminator (sodium thiosulfate), and the degradation effect of the sample on OTC was compared and analyzed by high performance liquid chromatography. The degradation results are shown in Figure 2 , wherein the Cu obtained by the preparation method provided by the present invention 0 -CuFe x O y The iron-copper bimetallic complex has the best degradation effect on OTC.
[0056] The Cu obtained in Example 2 0 -CuFe x O y The iron-copper bimetallic composite and the samples obtained in Comparative Examples 1-3 were subjected to XRD analysis. The main component of the sample prepared in Comparative Example 1 was CuO, the main component of the sample prepared in Comparative Example 2 was Fe2O3, and the component of the sample prepared in Comparative Example 3 was CuFe2O4. The main component of the material obtained in Example 2 was CuFe2O4, and it also contained some Cu compounds and Fe oxides. 0 -CuFe x O y The XRD patterns of the iron-copper bimetallic complexes prepared by adding different reagents were discussed, such as Figure 3 As shown in the figure, it can be seen that when only potassium borohydride is added during the preparation process, Cu 0 and its compounds; when only carbon nanotubes are added, the material obtained not only forms CuFe2O4, but also generates some Cu compounds and Fe oxides. However, when too much Fe oxide is generated, the catalytic performance of the material will be reduced; when carbon nanotubes are added first and then potassium borohydride during the preparation process, the added potassium borohydride will increase the Cu 0 The content reduces the production of Fe oxides and further improves the catalytic performance of the material.
[0057] XPS was used to characterize the material (Cu 0 -CuFe x O y Taking the iron-copper bimetallic complex as an example), the Cu 0 -CuFe x O y The element composition and valence state of the material are taken as an example of the material prepared in Example 2. The results are as follows Figure 4 As shown. Figure 4 It can be seen that Cu 0 -CuFe x O y It is mainly composed of three elements: Fe, Cu and O. And XRD did not detect C, indicating that after calcination, there are basically no carbon nanotubes in the material.
[0058] EDS Mapping was used to characterize and analyze the materials (Cu 0 -CuFe x O y Taking the iron-copper bimetallic complex as an example), the Fe element ( Figure 5 )、Cu element( Figure 6 )、O element( Figure 7 )、C element( Figure 8 ) was characterized and it can be observed that Fe, Cu, and O are evenly distributed on the surface of the material, while the distribution of C element does not match the shape of the scanning area, indicating that there are basically no carbon nanotubes in the material, which is verified by the analysis results of XPS and XRD.
[0059] The surface morphology of the materials obtained in Comparative Example 3 and Example 2 was analyzed and compared using SEM. Fig. 9 and 10 As shown in the figure, the surface of CuFe2O4 is a block structure, and a small amount of uneven crystal particles are attached to the surface. 0 -CuFe x O y The surface of the material is grooved and has relatively uniform crystal particles attached. This indicates that Cu 0 -CuFe x O y It has a relatively large specific surface area, which allows the material to provide more reaction sites during the reaction.
[0060] The specific surface area and pore size distribution of the material were characterized by BET (Cu obtained in Example 2 0 -CuFe x O y For example, the iron-copper bimetallic compound Fig.11and 12 , Cu 0 -CuFe x O y The desorption curve of Cu belongs to type IV isotherm, and the H3 hysteresis loop can be clearly observed. 0 -CuFe x O y The surface may be a micro-void / mesoporous structure. At the same time, after calculation and analysis, Cu 0 -CuFe x O y The specific surface area is 5.8 m 2 / g. This shows that Cu 0 -CuFe x O y The larger surface area can provide a large number of active sites for activating PMS.
[0061] The electrochemical performance of the materials obtained in Example 2 and Comparative Examples 1-3 was tested by electrochemical impedance spectroscopy (EIS) to analyze their electron transfer capabilities. The semi-arc diameter in the electrochemical impedance spectrum reflects the electron transfer capability of the material. The smaller the semi-arc diameter, the stronger the electron transfer capability of the material. Fig.13 As shown in the figure, the order of EIS semi-arc diameters of several materials is: CuFe2O4>Fe2O3>CuO>Cu 0 -CuFe x O y . Description Cu 0 -CuFe x O y The material has a more superior electron transfer ability, which once again confirms its superior catalytic performance.
[0062] Take five groups of 200mL OTC reaction solution (initial OTC concentration is 20mg·L -1 ) were placed in a low-temperature thermostatic bath or a thermostatic water bath, the reaction temperature was controlled at 25°C, and the initial pH values of the reaction solution were adjusted to 3, 5, 7, 9, and 11 using NaOH solution and dilute H2SO4 solution. 0 -CuFe x O y The iron-copper bimetallic complex was reacted with 25 mg / L and 0.1 mmol / LPMS, and the time was set. 3 mL of the sample was taken at the set time interval, quickly mixed with the reaction terminator (sodium thiosulfate), and the degradation effect of the sample on OTC was compared and analyzed by high performance liquid chromatography. The degradation results are shown in Fig.14 As can be seen from the figure, the Cu 0 -CuFe x O yThe iron-copper bimetallic complex can be used in a wide pH range.
[0063] The catalytic material was repeatedly recovered and the experiment was repeated multiple times (using the Cu obtained in Example 2 as 0 -CuFe x O y For example, the iron-copper bimetallic complex was found to contain Cu 0 -CuFe x O y It has strong catalytic stability. Fig.15 As shown in the figure, when the third cycle experiment was carried out, the degradation rate of OTC was still as high as 90.2% at 45 min. When it continued to the fifth cycle, the degradation rate of OTC decreased to 83.1%. 0 -CuFe x O y It has strong continuous catalytic ability and superior catalytic stability, which lays a solid theoretical foundation for the practical application of this material.
[0064] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A Cu 0 -CuFe x O y The preparation method of the iron-copper bimetallic composite is characterized by: The following steps are involved: S1. Prepare a mixed solution of Fe(NO3)3 and Cu(CH3COO)2 with a molar ratio of Fe:Cu of 2:1 in advance, and adjust the pH value of the mixed solution to 9; S2, according to the amount of the mixed solution in S1, add carbon nanotubes in an amount of 2.5-5g / L, stir evenly, then add KBH4 in an amount of 2.5-5g / L, and stir evenly, wherein the KBH4 is prepared into a solution and added dropwise; S3, after the KBH4 solution was added, the reaction was continued at 90°C with stirring for 4 h to obtain Cu 0 -CuFe x O y Sol; S4, the obtained Cu 0 -CuFe x O y The sol was subjected to high temperature treatment, calcined at 400-600°C, and kept at this temperature for 180 min to obtain Cu 0 -CuFe x O y Material.
2. The preparation method according to claim 1, characterized in that: Ammonia water was used to adjust the pH in S1.
3. The preparation method according to claim 1, characterized in that: In S3, the reaction temperature was maintained at 90° C. by water bath heating and mechanical stirring for 4 h.
4. The preparation method according to claim 1, characterized in that: The initial temperature rise rate in S4 is 10°C / min.
5. A kind of Cu 0 -CuFe x O y Iron-copper bimetallic composite, characterized by: The method is prepared by any one of claims 1 to 4.
6. A Cu as claimed in claim 5 0 -CuFe x O y The application of iron-copper bimetallic complex in persulfate advanced oxidation technology has a pH range of 3-11.